Assessment of growth and fermentation of some yeasts on soybean residue hydrolysate - Thi Van Anh Mai; Kim Loan Nguyen; Dinh Trien Dang; Thi Xuan Sam Nguyen; Thanh Hang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2023)
This study explored the growth and fermentation capabilities of four distinct yeast strains, including Saccharomyces cerevisiae var. boulardii CNCM I-745, S. cerevisiae 7012, S. cerevisiae 7028, and S. cerevisiae var. diastaticus BE-134, with the aim of identifying the most suitable strain for the production of a fermented beverage from soybean residue hydrolysate (SRH). The results were as follows: S. cerevisiae 7012 exhibited the most efficient fermentation, with residual sugar content of 2.16 g/100 ml, an ethanol concentration of 1.39% v/v, and a favourable aroma, receiving a sensory score of 4.3/5 points. Within this sensory profile, the aromatic compound 2-phenylethanol was found to be the predominant component. Additionally, S. cerevisiae var. boulardii CNCM I-745 demonstrated superior biomass production ability, achieving a cell density of 7.71 log CFU/ml after 48 hours of fermentation solution also showed the highest antioxidant activity, equivalent to 1.63 mg of ascorbic acid per 100 ml. Consequently, these two yeast strains were selected for combined use in fermentation to leverage the probiotic characteristics of S. cerevisiae var. boulardii CNCM I-745 and the flavouring capacity of S. cerevisiae 7012 in creating fermented beverages from SRH.